Abenaki materials, Miscellaneous Manuscripts Collection - Leland, Marine (1956)
"Mrs. Johnson's narrative of her captivity," a talk for the Canadian Broadcasting Corporation based on Mrs. Johnson's narrative of her captivity by the Abenaki in 1754-1758.